Determining the effectiveness of covering conifer seedlings in spring - Kiseleva Elena; Rachenko Maxim; Rachenko Anna (E3S Web of Conferences)
Forests play a key role in regulating water balance, they prevent shallowing of rivers, removal of small particles of soil and sand into rivers, and soil erosion. The region is mainly inhabited by the following coniferous trees: Picea obovata Ledeb., Pinus sylvestris L., Larix sibirica LEDEB., Pinus sibirica Du Tour, и Abies sibirica LEDEB. Concerning reforestation, the Irkutsk region is one of the leaders in the country. Research in the field of reforestation is relevant and important for the region. The given research examined various time frames and methods for obtaining high-quality planting material by seed propagation. Seeds of coniferous trees were collected from September to March (depending on the type of plants). Sowing was carried out under artificial climate conditions and in open ground, both in autumn (under the snow) and in spring. To prevent soil drying out, several methods of covering seeds in spring were examined (tunnels and coulisse planting were used). As the result of the research, the optimal for the region time frames and methods for sowing conifer seeds were determined.